A Peep into Children’s World - Sharma, Smriti (THE PRIMARY TEACHER, 2018)
Empirical research studies on children and childhood from socio-cultural and ecological perspectives are in their nascent stages across the world, especially in India. The present research was aimed at understanding which/what living beings and objects children of ages 7–10 consider of utmost importance to them. Data were collected from a total of 346 children studying in two selected private-run and government-run schools in Delhi using a structured questionnaire presented in the form of a worksheet. A mixed methods approach was used to analyse the data using the process of thematic coding and subsequently applying descriptive statistics to find out prominent patterns, and ascertain the influence of gender and type of school on the responses of the children. The findings are presented in the sub-sections of—‘most important living being’ and ‘most important thing or object’. The analysis indicates significant differences in the responses of children according to the type of school—government and private.